Implementasi Peraturan Daerah Kabupaten Padang Lawas Utara Nomor 6 Tahun 2016 Tentang Penyimpanan Sementara Limbah Bahan Berbahaya Dan Beracun Perspektif Siyāsah Dustūriyyah - Hsb, Hilal Ramadhan; Iwan (Borneo : Journal of Islamic Studies, 2025)
The management of hazardous and toxic waste (B3) in Padang Lawas Utara Regency remains problematic and has yet to find an effective resolution. One of the main issues is environmental pollution in the Barumun River, caused by waste disposal from PT. Sumber Sawit Nusantara (SSN). This contamination has led to community unrest, as residents living along the river can no longer use the water for daily activities such as bathing and washing. To address this issue, the local government of Padang Lawas Utara implemented an environmental management policy through Regional Regulation No. 6 of 2016, which is analyzed in this study from the perspective of siyāsah dustūriyyah. This research employs a juridical-empirical approach, combining both primary and secondary data. The findings indicate that the management of hazardous and toxic waste (B3) has not been optimally implemented due to the lack of compliance with the regional regulation. This condition is exacerbated by insufficient education and socialization efforts by the government, particularly toward factory operators in Sionggotan Village, Simangambat District. Therefore, greater emphasis on environmental education, public legal awareness, and consistent law enforcement is essential to achieve sustainable hazardous waste management in the region.